Persepsi Konsumen Muslim Terhadap Produk Ms Glow yang Bersertifikat Halal di Surabaya - Wulan Daru, Nadia; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2019)
Ms Glow is a beauty product that already gained halal certification on their products. As Muslim consumers, we must be selective in choosing beauty product that will be used in daily and proper with Islamic law. This research used qualitative descriptive method that aimed to find out Muslim consumers’ perception towards halal certification of Ms Glow beauty product. The findings of this research indicate that Muslim consumers have two perceptions, which are care and care less about halal certification. Muslim consumers who care about it are consumers who need all of Ms Glow products labelled with halal certification on the packaging even though they do not use it. Where as Muslim consumers who care less are consumers who does not concern about halal certification in all Ms Glow products, and they still use it.